Checklists of extant harvestman (Arachnida: Opiliones) species for all the countries of the world - Kury, Adriano B.; Kury, Ian S.; Oliveira, Ana Beatriz R. De (Zootaxa, 2024)
This study presents a comprehensive survey of the extant diversity of harvestmen (Arachnida: Opiliones), a pivotal taxon for biogeography and conservation studies, across Earth’s geopolitical entities (here treated as "countries"). The rationale for recognizing more than 200 of these countries lato sensu worldwide is provided. The four most diverse of these countries are here further subdivided in states/provinces resulting in over 300 controlled vocabulary terms (geographic areas that contain harvestman records). These terms have been tagged to over 6900 species/subspecies of Opiliones, resulting in the generation of over 10,000 records. Checklists aiming for exhaustiveness are presented for valid extant Opiliones species/subspecies in each of these geographic areas, as documented in the World Catalogue of Opiliones (WCO) project, and geo maps are included to visually depict the distribution density of known species. Notably, this work marks the first-ever presentation of such checklists in the taxonomic literature for several countries, notably India, Indonesia, Papua New Guinea, and the Philippines. Brazil emerges as the most diverse country for harvestmen, with more than 1000 species, followed by Venezuela, Indonesia, and the United States, each hosting over 300 species. Checklists are individually provided for each state/province in these four countries. Elusive yet valid species are listed separately in their own section of nomina dubia, not entering the countries lists. Leiobunum rotundum argentatum Franganillo, 1926, is here elevated to Leiobunum argentatum Franganillo, 1926 new rank. Paropilio spinipes Roewer, 1956, is considered a junior subjective synonym of Opilio cirtanus C.L. Koch, 1839 syn. nov., Lacinius longisetus (Thorell, 1876) is considered a junior subjective synonym of Lacinius horridus (Panzer, 1794) syn. nov. The combination Rhopalocranaus hickmanni Caporiacco, 1951, is reinstated after this species appeared as Cranaus hickmanni in the literature. Some nomenclatural changes are established as a consequence of homonymy: (a) Paranemastoma graecum (Giltay, 1932) comb. nov. is the correct name for Nemastoma simplex Giltay, 1932 (currently combined as Paranemastoma simplex), a junior primary homonym of Nemastoma bacilliferum simplex Simon, 1913; (b) Belemulus annulatus remains permanently invalid as a junior secondary homonym replaced before 1961, so the replacement name to be used is Belemulus roeweri (Soares & Soares, 1948) comb. nov.; (c) Isaeus mexicanus Sørensen, 1932, must be reinstated as a species-group name rejected after 1960 due to secondary homonymy with Haehnelia mexicana Roewer, 1915; (d) Paranemastoma roeweri Staręga, 1978 is the correct name for Nemastoma redikorzevi Roewer, 1951, a junior primary homonym of Nemastoma redikorzevi Kharitonov, 1946; (e) the new name Neocynorta lanegra nom. nov. is proposed for Neocynorta lata (González-Sponga, 1992), originally Cynorta lata, which is a primary homonym of Cynorta lata Banks, 1909, currently in the genus Eucynortula; (f) the new name Neocynorta electrigena nom. nov. is proposed for Neocynorta punctata (González-Sponga, 2003), originally Paecilaema punctata, which is a primary homonym of Paecilaema punctata Sørensen, 1932, currently in the genus Anduzeia.